Fraxinus xanthoxyloides leaves reduced the level of inflammatory mediators during in vitro and in vivo studies. Issue 1 (December 2016) - Younis, Tahira; Khan, Muhammad; Sajid, Moniba; Majid, Muhammad; Zahra, Zartash; Shah, Naseer
Abstract Background Different parts ofFraxinus xanthoxyloides Wall. (Oleaceae) are used traditionally in the treatment of internal wounds, bone fracture, pain, jaundice, malaria and in pneumonia. These ailments involve protective and essential mechanisms of the organism in response to infection, injury and trauma. However, prolonged inflammation may lead to inflammatory disorders. The present investigation was carried to evaluate the crude methanol extract ofF. xanthoxyloides leaves and its fractions for their anti-inflammatory and analgesic effects. Methods Methanol extract ofF. xanthoxyloides leaves was fractionated through liquid-liquid partition on escalating polarity of solvents. Acetic acid and thermal responses were used to evaluate the analgesic effects of extract/fractions in rat. Anti-inflammatory effects were monitored through in vitro; TNF-α activated NFkB in 293/NFkB-Luc HEK cells and LPS-activated nitric oxide (NO) assay in RAW 264.7 cells. For in vivo studies carrageenan induced paw edema model was used in rat. Both in vitro and in vivo studies have indicated that chloroform fraction exhibited superior anti-inflammatory effects to other extract/fractions and therefore, was used in air pouch model in rat to estimate the inhibition in leukocyte migration and synthesis of inflammatory mediators. In addition, phytochemical investigation of crude extract was carried out by GC-MS analysis. Results GC-MS studies of crude extract revealed the presence of various classes of which terpenoids (26.61 %), lactam (16.47 %), esters (15.81 %), phenols (8.37 %), and steroid (6.91 %) constituted the major categories. Among the extracts chloroform fraction (200 mg/kg bw) significantly (P <0.001) increased the percent latency time (76.13 ± 4.49 %) in hot plate test after 120 min and decreased (P <0.001) the count of writhes (77.23 ± 5.64 %) as compared to other extracts. The in vitro studies indicated that chloroform fraction at 15 μg/ml more effectively inhibited the TNF-α induced synthesis of NFkB (85.0 ± 8.12 %, IC50  = 5.98 μg/ml) and LPS-instigated nitric oxide (78.23 ± 2.39 %, IC50  = 6.59 μg/ml) synthesis. Although all the extract/fractions showed a dose dependent increase in inhibition of edema formation however, chloroform fraction (4th h = 77.64 ± 3.04 %) at 200 mg/kg bw exhibited relatively higher (P <0.001) anti-inflammatory activity in carrageenan-induced paw edema in rat. Moreover, chloroform fraction had the ability to decrease (P <0.001) the influx of leukocytes and the concentration of inflammatory mediators; TNF-α, NO, IL-6 and PGE2 in air pouch exudate. Conclusion The study demonstrates the therapeutic potential ofF. xanthoxyloides leaves against the inflammatory disorders suggesting the presence of active constituents in chloroform fraction.